Theoretical and Empirical studies of Economic Growth Processes of Agricultural Production in Russian Federation - Anokhina, Marina Yegorovna; Zinchuk, Galina Mikhailovna; Butov, Aleksandr Vladimirovich (International Journal of Economics and Financial Issues, 2017)
Based on the analysis of the economic growth theories, economic cyclicality and industrial markets the article presents a concept of economic growth of industrial complexes. The concept focuses on factors, determinators and conditions of economic growth and their causal relationships, the latter being additional driving force of economic dynamics of an industrial complex. The practical aspects of the designed concept are shown on the example of the Russian agro-industrial complex (AIC). With account for the limitations of the present conditions which do not help provide for the essential functions of AIC as a subsystem of national economy, the authors identified the causes of insufficient economic dynamics of AIC. On the basis of the designed concept of economic growth of industrial complexes there were made conclusions about necessity to create growth conditions which, with appropriate balance of factors and growth determinators, will ensure quantitative, qualitative and reproductive dynamics of agro-industrial production. There have been devised strategic initiatives on managing economic growth of agro-industrial production at the stage of building-up sustainable dynamics and new quality of AIC growth. Keywords: economic growth; agro-industrial complex of Russian Federation; agro-industrial complex. JEL Classifications: j47, O14, Q01, Q18